GREEN ECONOMY IN UZBEKISTAN: PROBLEMS AND PROSPECTS - Khusainov Ravshan Rakhimovich (Scholar Express Journal, 2024)
This article examines the “green” economy from the point of view of Uzbekistan. The main task is to analyze the current situation in environmental and economic terms, as well as consider the prospects for the development of green technologies and innovations. The article provides recommendations for improving the situation and achieving more sustainable and environmentally friendly development
Keywords: Green economy; Uzbekistan; sustainable development